Starch properties and morphological differences of Oryza sativa mutants, MR219-4 and UPMTC1 - Yong, Wai Shin (2015)
Rice represents the staple food for nearly half of the world’s population. Efforts have been taken to produce rice cultivars with high yielding capacities and resistant to abiotic stresses to cope with the increased demand of rice. Previous studies showed that MR219-4, a Malaysian indica rice has good tissue culture responses. It also has enhanced tolerance towards drought and submergence as compared to MR219. UPMTC1, which was derived from MR219-4 had exhibited enhanced salt tolerant property than MR219-4. This study was carried out to determine the starch properties and morphological differences between MR219-4 and UPMTC1, which included morphological traits, soluble sugar content, starch content, apparent amylose content (AAC), starch disintegration properties, protein concentration and determination of starch synthase activity. Results showed that there were significant differences between plant height of MR219-4 (107.9cm) and UPMTC1 (79.3cm), and panicle length between MR219-4 (26.4cm) and UPMTC1 (22.3cm) at day 110; however; there were no significant differences between the number of tillers, flat length length and width, culm length, days to maturity and weight of 500 grains of MR219-4 and UPMTC1. The decrease in starch content of MR219-4 and UPMTC1 at germination day seven were 45.0% and 11.2% respectively. The apparent amylose content of MR219-4 and UPMTC1 were 22.19% and 25.37% respectively. UPMTC1 which has higher AAC may be suitable to be used as low glycemic diet for type two diabetic patients. Both MR219-4 and UPMTC1 exhibited resistant to starch disintegration towards alkali solution, suggesting both have high gelatinization temperature. However, further studies need to be carried out towards MR219-4 and UPMTC1 as both rice cultivars have the potential to be planted on a commercial scale.